2023
DOI: 10.1108/tlo-11-2022-0137
|View full text |Cite
|
Sign up to set email alerts
|

Influence of quality of work life on psychological capital of organizational leaders using artificial neural networks: a study on learning in hybrid workplace

Abstract: Purpose The COVID-19 pandemic has greatly impacted work, leading to the adoption of remote work practices and changes in power dynamics and trust. Although managing remote work has received much attention, the impact of the quality of work life on the effectiveness of hybrid workplaces has been less studied. This study aims to examine the relationship between quality of work life and psychological capital among organizational leaders using an artificial neural network (ANN) model. Design/methodology/approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…However, it is also important to determine how the quality of work life affects the psychological capital of leaders in a hybrid environment. Rahul Paul & Khalid Perwez (2023) found that this relationship is positive, i.e. quality of work life has a positive impact on leaders' psychological capital.…”
Section: Quality Of Work Life Of Leadersmentioning
confidence: 91%
See 2 more Smart Citations
“…However, it is also important to determine how the quality of work life affects the psychological capital of leaders in a hybrid environment. Rahul Paul & Khalid Perwez (2023) found that this relationship is positive, i.e. quality of work life has a positive impact on leaders' psychological capital.…”
Section: Quality Of Work Life Of Leadersmentioning
confidence: 91%
“…The dearth is even greater when it comes to the impact of quality of work life on the effectiveness of leaders. Rahul Paul & Khalid Perwez (2023) addressed this gap by examining the relationship between quality of work life and leaders’ psychological capital using an artificial neural network model. The study of managers is worthwhile because their contribution to organizational performance is undeniable, both positive and negative.…”
Section: Quality Of Work Life Of Leadersmentioning
confidence: 99%
See 1 more Smart Citation